Book Review: JEN GILBERT. Sexuality in School: The Limits of Education. (2014) - Bliss, S. A.; Husband, Marc (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
JEN GILBERT. Sexuality in School: The Limits of Education. Minneapolis, MN: University of Minnesota Press. (2014). 144 pp. $20.00 (paperback). (ISBN 978-1-4529-4222-3)